A comparison of two short-term intensive physical activity interventions: methodological considerations - Norton Lynda H; Norton Kevin I; Lewis Nicole; Dollman James (BMC, 2011)
Abstract Background Increases in chronic illness due to sedentary lifestyles and poor metabolic fitness have led to numerous intervention strategies to promote physical activity (PA). This paper describes the methodological strategies of two short-term PA interventions. Outcome measures reported are PA adherence and compliance rates during the intervention and at 3, 6 and 12-month follow-up. Methods The 40-day interventions were: a pedometer-based walking program (n = 251) and a group-based intensive program (n = 148). There was also an active control group (n = 135). Intervention subjects were prescribed PA each day and required to record all activity sessions (pedometer steps or energy expenditure from heart rate monitors). Results Compliance (≥ 150 min/wk PA) was highest post-intervention (81.1% and 64.5% for the group and pedometer subjects, respectively) and then progressively decreased across the 12-month follow-up period (final compliance rates were 53.5% and 46.6%, respectively) although they remained significantly higher than pre-intervention rates (zero %). There was significantly higher adherence to 6 months (75.0% and 64.9%), and compliance to 3 months (64.9% and 51.0%), for group versus pedometer subjects. The active control group maintained the highest adherence and compliance rates across the study. Conclusions The group-based program resulted in higher adherence and compliance rates post-intervention although both types of interventions showed long-term effectiveness to increase activity patterns.